2021
DOI: 10.46303/ressat.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Educating Progressed Learners in Times of COVID-19: How Can Bricolage Help?

Abstract: This paper discusses using bricolage to mitigate the struggles faced by progressed learners in rural KwaZulu-Natal, South Africa, in the context of the global COVID-19 pandemic. Most progressed learners perform poorly in many subjects, especially sciences. Their struggle has stimulated the need to find ways to enhance their performance. Reinvented artefacts and processes can be used for emancipation, and to transform agendas for improving the performance of progressed learners. To collect data, we used partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…CER anchors the study, with its recognition of the important principles of social justice and equality being grounded within the critical theory paradigm [56]. erefore, the study reported in the present article was conducted in schools within the rural context of KwaZulu-Natal, with the marginalised voices of the school leaders involved being amplified through the CER principles of equality, participation, social justice, and human emancipation [56,57].…”
Section: Methodsmentioning
confidence: 99%
“…CER anchors the study, with its recognition of the important principles of social justice and equality being grounded within the critical theory paradigm [56]. erefore, the study reported in the present article was conducted in schools within the rural context of KwaZulu-Natal, with the marginalised voices of the school leaders involved being amplified through the CER principles of equality, participation, social justice, and human emancipation [56,57].…”
Section: Methodsmentioning
confidence: 99%
“…This quick shift triggered inequity in the education system as the level of support for all learners depends on the ability to conduct lesson online. While this could have been an opportunity to enhance digitalisation in education, Dube and Ndaba (2021) asserts inequality and disparity between schools was visible during the pandemic. This division affected schools in rural areas were progressed learners are dominant.…”
Section: Literature Review Curriculum Support Plan For Learner Progre...mentioning
confidence: 99%
“…Learners who would have failed the senior phase because of not meeting the minimum pass requirements (DBE, 2016) were condoned in senior phase mathematics and promoted to the FET phase. Many of these progressed learners achieve below par in various subjects, specifically sciences, including mathematics (Dube & Ndaba, 2021).…”
Section: Introductionmentioning
confidence: 99%